Risk stratification of postoperative complications in jaundiced patients with focal diseases of the biliopancreatoduodenal zone - Muraviov, P.; Zaporozhchenko, B.; Borodaev, I.; Shevchenko, V.; Zaporozhchenko, M.; Harhouri, Makrem (Journal of Education, Health and Sport, 2021)
The risk stratification was performed by mathematical modeling taking into account genetic factors and the results of instrumental research as ultrasonic elastography. The results of 272 jaundiced patients’ surgical treatment as pancreaticoduodenal resection (PDR) for malignant tumors of biliopancreatoduodenal area (218 patients) and chronic pseudotumoral pancreatitis (54 patients) were analyzed. In the main group (n=112) the optimized algorithm of preoperative preparation and risk stratification was used and in the comparison group (n=160) preparation for PDR was carried out conservatively according to generally accepted standards. radical surgery is defined as inexpedient and too risky, while shunt decompression surgery is performed as a first step for pancreatoduodenal resection. Thanks to the preoperative preparation according to our algorithm, mental status evaluation in the main group compared to the comparison one was significantly better. By MoCA scale before surgery it was 24.9 ± 3.2 and 22.8 ± 2.4 points, and by the DSST test - 40.2 ± 3.8 and 23.6 ± 2.6 points in the main and comparison groups respectively. The level of bilirubinemia in patients of the main group on the day before PDR was 112.3±2.7 μmol/l, while in the comparison one it was 198.3±3.3 μmol/l (p <0.05). On the eve of the PDR, the activity of alkaline phosphatase was in the main group 104.8 ± 1.3 U / l, and in the comparison group - 270.8 ± 1.9 U / l (p <0.05). Before PDR, γ-glutamiltransferase activity significantly decreased to 529 ± 29 U / l in the comparison group and to 485 ± 33 U / l in the main group (p <0.05).